Differences in Effective Reading Speed of Fiction and Nonfiction Texts Among Eighth Grade Students at SMP Negeri 5 Ukui Pelalawan Regency - Rosida, Mia Fatma; Septyanti, Elvrin; Zulhafizh, Zulhafizh (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to describe differences in effective reading speed between fiction and nonfiction texts among eighth grade students at SMP Negeri 5 Ukui using a descriptive quantitative approach. Data were collected through reading speed tests and comprehension tests based on cognitive aspects of reading literacy. Data analysis employed a paired t test. The results showed that students’ effective reading speed in nonfiction texts, with an average score of 124.33, was higher than in fiction texts, which averaged 119.14. These findings indicate that text type significantly influences students’ reading ability, and teachers are encouraged to provide balanced and intensive practice.